PENGARUH KONSEP DIRI, KEMANDIRIAN, MOTIVASI DAN LINGKUNGAN BELAJAR TERHADAP PRESTASI BELAJAR EKONOMI SISWA KELAS XI IPS SMA NEGERI DI KABUPATEN GRESIK - Wiyani, Tri Ervina Kristi (UNIVERSITAS NEGERI SURABAYA, 2013)
This study aimed to determine the effects of self-concept, self-reliance, motivation and learning environment for economic achievement in grade XI of Social class of all State Senior high schools in Gresik for academic year 2012/2013. Population was 821 students. Sample was 269 students selected by using sampling technique simple random sampling. Data were collected by questionnaires and documentation methods. The method of analysis in this study was a quantitative analysis, the multiple linear regressions. Results showed there is no partial effect on self-concept to achievement of economic, there is a partial effect on the learning achievement of economic independence, there is a partial effect on the learning achievement of economic motivation, there is no partial effect of learning environment for economic achievement, and there are no simultaneous effect on self-concept, self-reliance, motivation and learning environment on the learning achievement of economic